Fetal and infantile hypertension caused by unilateral renal arterial disease. Issue 8 (August 1990) - Wilson, D I; Appleton, R E; Coulthard, M G; Lee, R E; Wren, C; Bain, H H
Abstract : Three children who presented with heart failure in infancy caused by severe hypertension as a result of unilateral renal arterial disease are described. One presented at 3 days of age with persistent fetal circulation and heart failure. He had abnormal great vessels that indicated that the hypertension was of long standing and therefore fetal; this has not been described previously. The other two children failed to thrive because of unrecognised hypertension and subsequently presented with heart failure. All three underwent unilateral nephrectomy which cured their hypertension, and all were thriving at the time of writing. The benefits of nephrectomy outweighed the operative risks and loss of renal function. Blood pressure should be measured in children who are failing to thrive as part of routine clinical practice.